Water Sanitation and Human Settlements: Crisis, Opportunity or Management? - Gyawali, Dipak (Water Nepal, 2004)
Water problems are as diverse as the human settlements that depend on water availability. In a region as large as Asia, the number of water-related problems is so vast that it is impossible to engage with any crisis, whether flood or drought, pollution or displacement, without paying homage to water. The region spans every known climatic and hydro-ecological zone, including deserts, tropical floodplains and tundra. The challenge of providing varied human dwellings in such diverse habitats with safe and reliable water, for both human consumption and economic activities promoting general well-being, will have to engage the sum total of known global ingenuity. Despite this diversity, it is necessary to identify and address common problems if we intend to forge any intelligent plan for collective action to solve water and settlement-related problems. This effort will require us to step back from specifics, which are different in every hamlet and town in every clime, and deduce general lessons. It is precisely in drawing such lessons that those of us engaged in redressing social or environmental wrongs face our biggest challenge. Water problems, especially those that pertain to social equity and environmental sanity are often very local concerns that demand actions at the local level, but regional and global cooperation on such local issues are difficult to define unless the problems have been generalised for a global audience. This generalisation is not an easy thing to do, but without it, no agreement is possible on how to proceed forward with collective action. Social and environmental activists are intimately in touch with their grassroots and they function most effectively in local situations. But, in all honesty, they are not very effective at the global level where they have to confront problems abstracted to several levels above the grassroots. Often, activists find themselves confronting a situation in which the issues that they have dealt with at the field level have been re-cast in such a manner that they are hardly recognisable. In some cases of resetting, sharp multinational businessmen or their even sharper brethren in international bureaucracies will have already hijacked grassroots concern to suit their agendas. While it may be deeply self-satisfying to fulminate against them (as activists are prone to) denunciation alone will not push forward the common agenda of social and environmental justice. This essay addresses the business of deducing general conclusions for collective action. The effort first requires addressing the process of defining the problem itself, which, perhaps unwittingly, pre-determines what the possible solution might be. It argues that the currently established approach to looking at water and its associated environmental and social problems is rife with serious flaws: the very definition of the problem is partial and biased, and hence attempts to rectify the malaise within such a paradigm lead to more problems in the future. Let us examine this hijacking of development through a few cases captured by the following examples. Water Nepal Vol.11(2) 2004 pp.5-18